Interpulse phase corrections for unbalanced pseudo‐continuous arterial spin labeling at high magnetic field. Issue 3 (6th June 2017) - Hirschler, Lydiane; Debacker, Clément S.; Voiron, Jérôme; Köhler, Sascha; Warnking, Jan M.; Barbier, Emmanuel L.
Abstract : Purpose: To evaluate a prescan‐based radiofrequency phase‐correction strategy for unbalanced pseudo‐continuous arterial spin labeling (pCASL) at 9.4 T in vivo and to test its robustness toward suboptimal shim conditions. Methods: Label and control interpulse phases were optimized separately by means of two prescans in rats. The mean perfusion as well as the interhemispherical symmetry were measured for several phase combinations (optimized versus theoretical phases) to evaluate the correction quality. Interpulse phases were also optimized under degraded shim conditions (i.e., up to four times the study shim values) to test the strategy's robustness. Results: For all tested shim conditions, the full arterial spin labeling (ASL) signal could be restored. Without any correction, the relative ASL signal was 1.4 ± 1.7%. It increased to 3.6 ± 1.4% with an optimized label phase and to 5.3 ± 1.2% with optimized label and control phases. Moreover, asymmetry between brain hemispheres, which could be as high as 100% without phase optimization, was dramatically reduced to 1 ± 3% when applying optimized label and control phases. Conclusions: Pseudo‐continuous ASL at high magnetic field is very sensitive to shim conditions. Label and control radiofrequency phase optimization based on prescans robustly maximizes the ASL signal obtained with unbalanced pCASL and minimizes the asymmetry between hemispheres. Magn Reson Med 79:1314–1324, 2018. © 2017 International Society for Magnetic Resonance in Medicine.